2021
DOI: 10.1155/2021/6659676
|View full text |Cite
|
Sign up to set email alerts
|

Shenlijia Attenuates Doxorubicin-Induced Chronic Heart Failure by Inhibiting Cardiac Fibrosis

Abstract: Application of the anticancer drug doxorubicin (DOX) is restricted due to its adverse, cardiotoxic side effects, which ultimately result in heart failure. Moreover, there are a limited number of chemical agents for the clinical prevention of DOX-induced cardiotoxicity. Based on the theories of traditional Chinese medicine (TCM) on chronic heart failure (CHF), Shenlijia (SLJ), a new TCM compound, has been developed to fulfill multiple functions, including improving cardiac function and inhibiting cardiac fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
3
1
0
Order By: Relevance
“…We reported an upregulation of Ccnd1 and Rarres1 following DOX treatment, consistent with previous studies [36,37]. Genes correlated with cardiac remodeling, such as Ace, Mmp13 and Ren1 were overexpressed in response to DOX treatment, typical of DOX-mediated myocardial damage [30,39,40]. We also observed that most of the apoptosis regulating genes are upregulated following DOX treatment compared to controls in both mCSs and hCSs, consistent with previous studies [30].…”
Section: Qpcr Analyses Of Cardiovascular Genes To Evaluate the Dox-in...supporting
confidence: 91%
See 1 more Smart Citation
“…We reported an upregulation of Ccnd1 and Rarres1 following DOX treatment, consistent with previous studies [36,37]. Genes correlated with cardiac remodeling, such as Ace, Mmp13 and Ren1 were overexpressed in response to DOX treatment, typical of DOX-mediated myocardial damage [30,39,40]. We also observed that most of the apoptosis regulating genes are upregulated following DOX treatment compared to controls in both mCSs and hCSs, consistent with previous studies [30].…”
Section: Qpcr Analyses Of Cardiovascular Genes To Evaluate the Dox-in...supporting
confidence: 91%
“…Ace, Mmp13 and Ren1 were similarly upregulated following DOX-mediated damaged. They all were upregulated in both mCSs and hCSs compared to control and were consistent with our I/R injury model and previous DOX mediated cardiac damage studies (table 2) [30,39,40].…”
Section: Cardiac Remodeling Genes Were Upregulated Following I/r Inju...supporting
confidence: 91%
“…However, some previous studies (Cui et al, 2017;Wang et al, 2019) showed that the left ventricular ejection fraction was less than 50%, indicating the successful modeling of heart failure. These findings are similar to those experimental heart failure models previously established (Bai et al, 2017;Wu et al, 2019;Sun et al, 2021;Wei et al, 2022;Xu et al, 2022;Suto et al, 2023). Furthermore, according to the design plan of this study, an echocardiogram test was performed after the construction of the CHF model, with the aim of screening the successfully modeled rats.…”
Section: Discussionsupporting
confidence: 91%
“…Shenlijia (SLJ) can improve cardiac function and inhibit MF progression. It improves cardiac function and ultrastructure, and inhibits MF development in DOX-induced CHF rats by upregulating extracellular matrix-metalloproteinase inhibitor (TIMP) expression ( 76 ) ( Figure 2 ).…”
Section: Molecular Mechanisms Of Chemoradiotherapy-related Cardiotoxi...mentioning
confidence: 99%